Waste management - Pradhan, Devesh (BIBECHANA, 2010)
Waste management has become very challenging in our society. Different types of wastes which are produced in our society have been investigated. Special attention has been given in the management methods of waste. Keywords: Industrial waste; Domestic waste; Composting; Recycling DOI: 10.3126/bibechana.v7i0.4048 BIBECHANA 7 (2011) 65-69